Research on Employees Negotiate Benefits and Strategies During Layoffs - He, Songyang (Transactions on Economics, Business and Management Research, 2024)
The COVID-19 pandemic has led to economic downturns globally, with many companies resorting to layoffs as a primary cost-cutting measure, resulting in a sharp increase in unemployment rates. However, improper termination of employment can have detrimental effects on the social economy, environment, and social security and can damage a company’s reputation, hindering its development. There is an ongoing debate about whether employees will choose to leave quietly or fight for their rights in the face of improper termination and the necessity of negotiation in such situations. Moving forward, it is crucial for governments to enhance relevant laws and regulations to protect workers’ rights. Companies must prioritize integrity and ethical practices in their employment decisions. Employees, on their part, should clearly understand their rights and engage in interest-based negotiations to protect their interests. By addressing these issues, the negative impacts of layoffs can be mitigated, leading to better outcomes for both employees and employers. This paper emphasizes the importance of a balanced approach to layoffs, advocating for stronger legal frameworks, corporate responsibility, and employee empowerment.